Plasma Levels of Total and Free Tissue Factor Pathway Inhibitor (TFPI) as Individual Pharmacological Parameters of Various Heparins - Alban, Susanne; Gastpar, Robert (Thrombosis and Haemostasis, 2001)
The release of circulating tissue factor pathway inhibitor (TFPI) into plasma by heparins is thought to contribute to their overall anti-thrombotic activity. In the presented study in healthy volunteers, we measured the heparin-induced increase of circulating total and free TFPI antigen and the aXa- and aIIa activity after subcutaneous (s.c.) injection of 9000 aXa-U of four different heparins: unfractionated heparin (UFH) (13.0 kDa), a medium molecular weight (MW) heparin with a narrow MW range (HF) (10.5 kDa), certoparin (6.0 kDa) and enoxaparin (4.5 kDa). Based on the administration of equi-active aXa doses, certoparin induced the highest increase in total TFPI determined as AUC (p <0.01). The lowest effect was observed for UFH (p <0.0001). However, the AUC of released free TFPI significantly increased in the order: enoxaparin < UFH < certoparin < HF, showing MW dependency with the exception of UFH. Comparing the effects of equi-gravimetric heparin doses, the MW dependency becomes even more pronounced. The mismatch of UFH may be due to its poor bioavailability, which becomes obvious from its low ex vivo aXa activity. In contrast to the TFPI releasing potency, the ex vivo aXa activity continuously decreased with increasing MW. Although the ex vivo aIIa activity of the heparins increased in the same order like the release of free TFPI, there was no clear correlation. This is attributed to the fact that the aIIa activity of heparin is not only dependent on the MW, but, in contrast to its TFPI releasing effect, also on the percentage of material with high affinity to AT. In conclusion, besides the aXaand aIIa activity, the TFPI releasing effect of heparins is an additional parameter of their individual pharmacological profile.
Keywords: TFPI; heparin; low molecular weight heparin; pharmacokinetics; pharmacological profile